Faktor Risiko Penyakit Skabies di Masyarakat - Heri Purwanto; Retno Puji Hastuti (Jurnal Kesehatan, 2020)
Scabies is an environmental-based contagious disease caused by mite infection "Sarkopes Scabiei Var Hominis". In the working area of Tanjung Sari Health Center, Natar Subdistrict, during 2014-2015, scabies was in third place in the top 10 contagious diseases. Every month an average of 12 sufferers (8,33%) per month are found, distributed in all age groups (0-5 years to ≥65 years). This study aims to determine the risk factors for scabies in the community by using a 1: 1 case-control design. Cases are people who have had scabies, while community controls who have never had scabies. The results of the study, the proportion of case and control groups who had risk factors for scabies in sequence: education level (82,5% and 68,0%), living habits (39,2% and 17,5%), physical environment (45,4% and 5,2%), biological environment (66,0% and 46,4%), social environment (56,7% and 3,1%), knowledge (72,2% and 36,1%), attitudes (12,4% and 6,2%), actions (86,6% and 52,6%), and sanitation (93,8% and 42,3%) There have eight risk factors that statistically show a significant relationship (p-value <0,05), i.e. level of education, living habits, physical environment, biological environment, social environment, knowledge, actions, and sanitation factors. Respondents with a bad social environment have a risk of sick scabies 41,03 times greater than respondents with a good social environment, sanitation that does not qualify as a risk of 20,72 times greater than those that meet the required sanitation, a dense physical environment has a risk of 15,28 times greater than the physical environment is not dense.